Students' Intentions to Use E-Learning during the Covid-19 Pandemic: An Extended Technological Accaptance Model (TAM) Approach - Purwandari, diah - (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
Online learning is a technology-based system, hence a process is required to ensure that students can embarace the technology, as the success or failure of a technology is determined by how well the user accepts it. Therefore, understanding the factors that drive the use of online learning is essential. This study aims to contribute to the literature on online learning in higher education during the COVID-19 epidemic by investigating the relationship between self-awareness and student acceptance of online learning. Several hypotheses were constructed using the TAM Model to investigate the relationship between the TAM construct and self-awareness as an antecedent. This study employed structural equation modeling (SEM-PLS) to investigate how 390 students in East Jakarta used online learning. The findings of this study revealed that self-awareness had a significant effect on perceived usefulness, perceived ease of use, and attitude, but it had no direct impact on the intention to continue using e-learning. Students' attitudes were considerably influenced by perceived usefulness and perceived ease of use. Perceived usefulness was the most influential factor on student attitudes, and attitude was a strong predictor of intention to continue utilizing online learning. The proposed model accurately predicted attitudes and intentions to continue to use e-learning.